Kesesuaian Penggunaan Obat Antidiabetes pada Pasien Diabetes Melitus di Puskesmas X Palembang - Ainun Wulandari; Resi Sukma Melati (Universitas Borneo Lestari, 2021)
Diabetes Mellitus is a metabolic disease characterized by hyperglycemia that insulin secretion disorders, insulin action or both. Diabetes Mellitus is one of four major non-communicable diseases that affect global health problems. The purpose of this study was to know the treatment profile and the suitability of giving antidiabetic drugs to diabetes Mellitus patients at the Health Center X, Palembang in 2020. This research is non-experimental research with a descriptive method and retrospective data collection. The data is taken from the medical records of patients at the Health Center X, Palembang in 2020. The results of the study used 138 samples, it was found that most patients in this study were female (55,07%), age range 56-65 years old (44,20%) and the most comorbidities, namely hypertension (48,55%). The most antidiabetic drug class was biguanide with the most drug being metformin (54,55%). The pattern of therapy at most was monotherapy with the most drug, namely metformin (73,91%). And to use polytherapy with two drugs with the highest combination of biguanide (metformin) and sulfonylurea (glimepiride) are (75%). The suitability of the use antidiabetic drugs of diabetes Mellitus patients with the appropriate drugs and dose category as much as 138 patients (100%).